Nursing and caring problems of a patient with gastric cancer - a case study - Majchrowicz, Bożena (Journal of Education, Health and Sport, 2023)
Gastric cancer is a malignant tumor that originates from the cells of the inner layer of the organ. It is characterized by a long asymptomatic period. The incidence of gastric cancer increases after the age of 50, especially in the male population. The aim of the study was to analyze selected aspects of nursing care provided to a patient after total gastrectomy in the course of gastric cancer. Materials and methods. The study used the case study method and an individual case study of a patient diagnosed with gastric cancer. Results and conclusions. The patient has problems in the biopsychosocial sphere. The role of a nurse in caring for a sick person is comprehensive care, education and preparation for self-care, and above all mental support. Constant monitoring of the patient’s health greatly helps to prevent possible complications.